2023
DOI: 10.1186/s12967-023-04089-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing and sequence of combining stereotactic radiosurgery with immune checkpoint inhibitors in treating brain metastases: clinical evidence and mechanistic basis

Abstract: Recent evidence has shown that immune checkpoint inhibitors (ICIs) are efficacious for treating brain metastases of various primary tumors. However, the immunosuppressive tumor microenvironment and the blood–brain barrier (BBB) or blood-tumor barrier (BTB) essentially restrict the efficacy of ICIs. Stereotactic radiosurgery (SRS) can be a powerful ally to ICIs due to its trait of disrupting the BBB/BTB and increasing the immunogenicity of brain metastases. The combination of SRS + ICI has shown synergy in brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…Patients with more immunogenic tumors and fewer immunosuppressive mechanisms at baseline may undergo productive immune activation upon irradiation. In contrast, nonresponding patients may harbor tumors adjacent to subverting immunity despite radiotherapy [29]. Further analyses incorporating tumor genomic and transcriptomic profiles along with circulating biomarkers could aid in testing this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with more immunogenic tumors and fewer immunosuppressive mechanisms at baseline may undergo productive immune activation upon irradiation. In contrast, nonresponding patients may harbor tumors adjacent to subverting immunity despite radiotherapy [29]. Further analyses incorporating tumor genomic and transcriptomic profiles along with circulating biomarkers could aid in testing this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review published by Tian et al reported improved outcomes for brain metastases when concurrent radiotherapy and immunotherapy were delivered in terms of clinical outcomes, but at the same time, the authors focused on the need for a precise definition of "concurrent administration" in terms of time intervals. Starting from an analysis of the biological mechanisms of both SBRT and immunotherapy, the authors hypothesized a peak in the immunogenic effect of high-dose radiotherapy within 24-72 h from the end of treatment, suggesting that right after this interval, immunotherapy has a higher benefit due to the radiotherapy boost effect [37].…”
Section: Discussionmentioning
confidence: 99%